Boundary plasma response in RFX-mod to 3D magnetic field perturbations. (August 2017) - Scarin, P.; Agostini, M.; Carraro, L.; Spizzo, G.; Spolaore, M.; Vianello, N.
Abstract: The edge of the RFX-mod (R = 2 m, a = 0.46 m) Reversed Field Pinch device is characterized by weak magnetic chaos affecting ion and electron diffusion. Edge particle transport is strongly influenced by a toroidal and poloidal asymmetry caused by magnetic islands and an ambipolar radial electric field ensures local neutrality. At higher plasma current (Iϕ >1MA) a spontaneous resonant dominant mode m/n = 1/7, slowly rotating, develops in the inner region. The edge electron pressure Pe and floating potential Vf show a shape of the Plasma Wall Interaction (PWI) with the same toroidal periodicity, which follows the edge local ideal magnetic displacement Δ1, 7 . Detailed measurements along the poloidal direction of Pe and Vf have been undertaken newly, their time behavior present respect to Δ1, 7 a time lag, which depends on the poloidal angle θ. The mode analysis in terms of helical angle reveals a role of the 0/7 mode in determining a poloidal phase lag respect to Δ1, 7 of Pe and Vf . Since the 0/7 is the largest toroidal sideband of the 1/7 mode, this work suggests a role of toroidal coupling in determining the plasma response to a MP. Highlights: Poloidal measurements of edge plasma pressure and floating potential. Analysis of edge plasma measurements in the helical angle frame. Effective local deformation of magnetic surfaces in the edge. Edge magnetic topology in RFP depends from m=1 stochastic layer and m=0 islands. Plasma response to a monochromatic MP depends on the toroidally coupled sidebands.